2015
DOI: 10.1088/1748-9326/10/1/014013
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and 137 Cs transport and accumulation in the Ogaki Dam of eastern Fukushima

Abstract: The Ogaki Dam Reservoir is one of the principal irrigation dam reservoirs in the Fukushima Prefecture and its upstream river basin was heavily contaminated by radioactivity from the Fukushima Daiichi Nuclear Power Plant accident. For the purpose of environmental assessment, it is important to determine the present condition of the water in the reservoir and to understand the behavior of sedimentsorbed radioactive cesium under different modes of operation of the dam, as these factors affect further contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The OC content of erosion sediments was around onethird of the OC content in irrigation water, and this difference in nutrient content was therefore caused by biogeochemical processes in the reservoir: breakdown of organic matter and nutrient mobilization in an aquatic environment contribute to the increased nutrient content of the irrigation water. Furthermore, sedimentation of the coarse, sandy material resulted in irrigation water containing fine-textured, fertile sediments higher in OC and N (Lick 1982;Yamada et al 2015). Results from Slaets et al (2015) on texture analysis for sediments in the same study site also demonstrated that irrigation water sediments were characterized by a finer texture (average 33 % sand, 33 % silt, 34 % clay) than those in overland flow (average 50 % sand, 30 % silt and 20 % clay).…”
Section: Reservoir Influence On Upland-lowland Nutrient Reallocation mentioning
confidence: 80%
“…The OC content of erosion sediments was around onethird of the OC content in irrigation water, and this difference in nutrient content was therefore caused by biogeochemical processes in the reservoir: breakdown of organic matter and nutrient mobilization in an aquatic environment contribute to the increased nutrient content of the irrigation water. Furthermore, sedimentation of the coarse, sandy material resulted in irrigation water containing fine-textured, fertile sediments higher in OC and N (Lick 1982;Yamada et al 2015). Results from Slaets et al (2015) on texture analysis for sediments in the same study site also demonstrated that irrigation water sediments were characterized by a finer texture (average 33 % sand, 33 % silt, 34 % clay) than those in overland flow (average 50 % sand, 30 % silt and 20 % clay).…”
Section: Reservoir Influence On Upland-lowland Nutrient Reallocation mentioning
confidence: 80%
“…Importantly, the fine particles, to which radiocesium is preferentially bound to, are the particles that are preferentially eroded and likely to be transported the farthest during erosive rainfall events (Govers, 1985;Malam Issa et al, 2006;Motha et al, 2002). Fundamentally, soil erosion and riverine transport processes are the primary factors governing the long-distance transfer of radiocesium from hillslopes to the Pacific Ocean Yamada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1). Because the upper part of the Ukedo River Basin has high levels of radiological contamination, several studies and analyses have been conducted in this basin to examine the features of 137 Cs transport from upstream to downstream (e.g., Kitamura et al 2014;Kurikami et al 2014;Yamada et al 2015). The annual 137 Cs discharge from the Ukedo River into the Pacific Ocean in the first few years after the FDNPP accident was approximately 2.0 TBq, the highest among rivers in the region (Oota River: 0.27vTBq, Odaka River: 0.13 TBq, Maeda River: 0.4 TBq, Kuma River: 0.28 TBq, and Tomioka River: 0.11 TBq) .…”
Section: Investigation Areamentioning
confidence: 99%
“…Understanding the features of 137 Cs transport from contaminated mountain forests to coastal sinks is key to the revitalization of marine industries. Therefore, evaluations of forest ecosystems and fluvial and lacustrine environments have been conducted (e.g., Funaki et al 2014;Yamaguchi et al 2014;Kitamura et al 2014;Kurikami et al 2014;Yamada et al 2015;Dohi et al 2015;Niizato et al 2016). 137 Cs distribution in shallow seas, which are major settlement areas for particle-sorbed 137 Cs, is a very important factor when studying 137 Cs transport from contaminated mountain forests to coastal sinks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation